Learn OpenCV 4 by building projects : build real-world computer vision and image processing applications with OpenCV and C++ - Millán Escrivá, David; Mendonça, Vinícius G.; Joshi, Prateek (Packt Publishing, 2018)
OpenCV is mainly used in Computer Vision and image processing and is considered to be one of the best open source libraries that helps developers focus on constructing complete projects on image processing, motion detection, and image segmentation. This book will be your guide to understanding the basic OpenCV concepts and algorithms.